Lift your impact : transform your mindset, influence and future to elevate your work, team, and life - Newman, Richard, 1977- (McGraw-Hill, 2023)
"Richard Newman's research into non-verbal communication and influence revealed something groundbreaking: small changes in how you communicate can create a massive difference in the way you are perceived by those around you"--